LONG-TERM FUNCTIONAL AND HISTOLOGICAL OUTCOMES OF RAT’S SCIATIC NERVE RECOVERY AFTER SEVERE INJURY AND EXPERIMENTAL TREATMENT WITH SILICON MICROWIRES - Likhodiievskyi, Volodymyr V.; Korsak, Alina V.; Olefir, Serhii S.; Zabila, Anna O.; Bukovska, Marya R.; Turiy, Marya V.; Klimovska, Alla I. (The Ukrainian Scientific Medical Youth Journal, 2018)
Severe peripheral nerve injuries both with traumatic limb amputations constitute a substantial part in all limb injuries especially during armed conflicts.For nerve grafting, nerve fibers alignment and fabrication of mind-controlled prosthetic limbs the concept of regenerative nerve implants with peripheral nerve interfacing was proposed. Silicon showed ideal properties not only for microelictronic devices fabrication but also as a favorable growth medium for neurons in vitro.This study aimed at evaluating the impact of silicon wires as a part of nerve conduit on motor and sensory recovery simultaneously with distal nerve stump neurotization using rat sciatic nerve injury model.Materials and methods. We performed experiments on 33 male Wistar rats that were divided into the following groups: I – sham-operated, II – those which received right sciatic nerve transection with 10 mm gap formation with autoneurografting, III – with 10 mm nerve gap bridged by allogenic decelullarized aorta with 4% carboxymethylcellulose hydrogel, IV – with 10 mm gap bridged by allogenic decelullarized aorta with 4% carboxymethylcellulose hydrogel and aligned p-type boron-ligated silicon wires.12 weeks after operation all rats were examined using von Fray filaments and by Walking track analysis method. For histological analysis right sciatic nerves were harvested. Frozen sections were stained with H&E and nitric silver impregnation was performed. At distal nerve stump nerve fibers density was calculated. The obtained results were compared using nonparametric statistical tests.Results. The histological analysis revealed differences in tissue reaction patterns between rats from autoneurografting group and conduit grafting groups.Histomorphometric data showed that nerve fibers density in rats from group IV was significantly higher than that in rats from group III (aorta+hydrogel grafting), but remained lower than in group II (autoneurografting).Morphometric data were supported by functional tests data: rats from group IV demonstrated higher values of SFI than those in group III and same as those in group II.Conclusions. According to histological and functional data we can presume that use of silicon wires as a part of hollow conduit improves results of injured sciatic nerve regeneration.